Real time monitoring and controlled power distribution system with SMART meter to support smart grid - Nayem, Md. Motiour Rahman; Mahmud, Fakhrul Islam; Rahman, Ashiq-Ur; Jahan, Tanver (BRAC Univeristy, 2017)
This thesis report is submitted in partial fulfillment of the requirements for the degree of Bachelor of Science in Electrical and Electronic Engineering, 2017.